2019
DOI: 10.3389/fmicb.2019.02489
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect and Mode of Action of Flavonoids From Licorice Against Methicillin-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus is a bacterial pathogen that causes food poisoning, various infections, and sepsis. Effective strategies and new drugs are needed to control S. aureus associated infections due to the emergence and rapid dissemination of antibiotic resistance. In the present study, the antibacterial activity, potential mode of action, and applications of flavonoids from licorice were investigated. Here, we showed that glabrol, licochalcone A, licochalcone C, and licochalcone E displayed high efficiency ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 49 publications
4
75
0
Order By: Relevance
“…Our inverse virtual screening applied in the present study proposes PBP2a to be the most possible target for the flavonoid class of compounds in our library. This in-silico suggestion is supported by a number of previous reports that illustrated flavonoids as possible modifiers of MRSA and other bacterial cell walls [18][19][20]. Further docking and molecular dynamic investigation not only confirmed the primary inverse virtual screening predictions but also revealed that some inactive derivatives can possibly modify the PBP2a allosteric site and hence, serve as adjuvants to reverse MRSA resistance toward β-lactams antibiotics (e.g., ampicillin 23).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our inverse virtual screening applied in the present study proposes PBP2a to be the most possible target for the flavonoid class of compounds in our library. This in-silico suggestion is supported by a number of previous reports that illustrated flavonoids as possible modifiers of MRSA and other bacterial cell walls [18][19][20]. Further docking and molecular dynamic investigation not only confirmed the primary inverse virtual screening predictions but also revealed that some inactive derivatives can possibly modify the PBP2a allosteric site and hence, serve as adjuvants to reverse MRSA resistance toward β-lactams antibiotics (e.g., ampicillin 23).…”
Section: Discussionsupporting
confidence: 76%
“…Surprisingly, this immune active site has a weak point of being under the control of another allosteric site in the same protein, and thus, targeting such a lateral binding site can make MRSA susceptible to their routine antibiotics once again (Figure 7). Previous reports have suggested a number of flavonoids as possible modifiers of MRSA cell wall and cell membrane [18][19][20]. Moreover, several polyhydroxylated flavonoids have demonstrated considerable synergistic effect with β-lactams antibiotics [16,21], and PBP2a has been suggested as the possible target [22].…”
Section: Discussionmentioning
confidence: 99%
“…Another antimicrobial agent targeting bacterial cell membranes are flavonoids including glabrol, licochalcone A, licochalcone C, and licochalcone E from licorice, the root and rhizome of Glycyrrhiza spp. They exhibit activity against methicillin-resistant S. aureus (MRSA), probably via binding to peptidoglycan, phosphatidylglycerol, and cardiolipin, dissipating proton move force, and increasing membrane permeability [67].…”
Section: Bacterial Skin Diseasementioning
confidence: 99%
“…Flavonoids are also well known for their antimicrobial capabilities. For example, it has been reported that glabrol, a flavonoid from licorice, displayed high efficiency against methicillin-resistant Staphylococcus aureus (MRSA) in both in vivo and in vitro models [6]. A new class of modified flavonoids namely apigenin and quercetin was found to completely inhibit the growth of Listeria monocytogenes, Pseudomonas aeruginosa, and Aeromonas hydrophila [7].…”
Section: Introductionmentioning
confidence: 99%